Analyzing Workflows and Improving Communication across Departments: A Quick and Simple Project Using Rapid Contextual Design. Issue 1 (19th May 2021) - Pascual, Jharina; Wallbank, Sarah
ABSTRACT: Analyzing workflows to identify problems and improve efficiency is a useful exercise, but a workflow analysis takes time and resources, particularly human resources. At the University of California, Irvine, two librarians in Technical Services used an adaptation of the Rapid Contextual Design methodology to create and execute a limited, low-barrier analysis to study the e-resources workflow between the Electronic Resources Unit, operating within the Acquisitions Department, and the Cataloging Department. Although limited in scope and time spent, the analysis provided insights that dispelled unfounded assumptions and pointed out several small, easily instituted changes to improve efficiencies, particularly by improving communication; the process also helped us prepare for gathering data and adjusting workflows for a pending migration to Alma and Primo. This presentation provides an overview of the methodology and describes how it was adapted and executed. It then describes the analysis results and actions taken.